Respuesta :
Step-by-step explanation:
[tex]3\left(x-4+1\cdot \:b\right)=8[/tex]
[tex]\mathrm{Divide\:both\:sides\:by\:}3[/tex]
[tex]\frac{3\left(x-4+1\cdot \:b\right)}{3}=\frac{8}{3}[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]x-4+b=\frac{8}{3}[/tex]
[tex]\mathrm{Subtract\:}b\mathrm{\:from\:both\:sides}[/tex]
[tex]x-4+b-b=\frac{8}{3}-b[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]x-4=\frac{8}{3}-b[/tex]
[tex]\mathrm{Add\:}4\mathrm{\:to\:both\:sides}[/tex]
[tex]x-4+4=\frac{8}{3}-b+4[/tex]
[tex]\mathrm{Simplify}[/tex]
[tex]x=-b+\frac{20}{3}[/tex]
[tex]\\ \rm\Rrightarrow 3(x-4+b)=8[/tex]
[tex]\\ \rm\Rrightarrow 3x-12+3b=8[/tex]
[tex]\\ \rm\Rrightarrow 3x+3b=20[/tex]
[tex]\\ \rm\Rrightarrow x+b=20/3[/tex]
[tex]\\ \rm\Rrightarrow x=20/3-b[/tex]